Design and Performance Evaluation of an IoT-Enabled Feed Level Alert System for Smart Fish Feeders - Micko Tomas; Baharuddin Baharuddin; Illa Aryeni; Elsi Alfionita Syawal; Muhammad Kodrat (Politeknik Negeri Batam, 2026)
The Feed Level Alert system on the Smart Fish Feeder was designed to monitor fish feed availability in real-time using an Internet of Things approach. Unlike previous research that focused solely on passive monitoring, this system presents a practical implementation equipped with automatic notifications when the fish feed level status reaches a set threshold. The HC-SR04 ultrasonic sensor is used to measure the distance between the tank lid and the feed surface, while the DHT-11 sensor monitors temperature and humidity to maintain feed quality. The ESP32 microcontroller is responsible for processing data and sending alert notifications via Telegram Bot with an average response time of 1,8 seconds. Test calibration results show a detection accuracy of 96,4% and a system reliability of 99,3%. The portable prototype design allows installation without significant mechanical modifications. With its integrative capabilities, this system shows high potential as an efficient, adaptive, and sustainable innovative aquaculture.